IMPLEMENTATION E-GOVERNMENT IN EMPLOYMENT MANAGEMENT INFORMATION SYSTEMIN THE REGIONAL OFFICE OF THE MINISTRY OF LAW AND HUMAN RIGHTS WEST JAVA, INDONESIA - Femmy Rismala Dewi; Andre Ariesmansyah; R. Hari Busthomi Ariffin; Regan Vaughan (International Journal of Social Science, 2022)
The development of information technology has an impact on government agencies to improve personnel administration services. Therefore, the Ministry of Law and Human Rights utilizes information and communication technology as a personnel management information system. This is a manifestation of the implementation of e-government in services in the field of personnel. This research use descriptive qualitative approach. Data collection techniques used are observation, interviews, and documentation. In this study, what under lies the implementation of e-government in the personne lmanagement information system is the existence of supporting factors for the success of e-government developed by Gil Gracia and Theresa (2005) which includes aspects such as data and information, information technology, managerial and organizational, legal and regulatory, institutional and environmental. The results of the study indicate that the implementation of e-government in the personnel management information system has been quite optimal but there is still a lack of employee awareness updating data. Efforts made at the Regional Office of the Ministry of Law and Human Rights West Java are always increasing employee awareness of the data update process.